Konsep Good Governance Dalam Transparansi Anggaran Dana Partai Politik Perspektif Fiqh Siyasah - Alfan, Thariq; Umam, Khotibul; Anwar, Iskandar Fahmi; Qomaruzzaman, Ahmad (Sosio Yustisia: Jurnal Hukum dan Perubahan Sosial, 2024)
The level of public trust in political parties in Indonesia is currently experiencing a decline due to the lack of transparency by political parties regarding financial reports, activities, and the membership structure of political parties. This is exacerbated by many individuals within political parties who are involved in corruption cases or misappropriation of party funds. As a result, the public expects that the budgets of political organizations must be transparent for the public to trust political parties, which are organizations that reflect the hopes and desires of society. The current study seeks to grasp political parties' attempts to attain budget transparency to actualize the concept of good governance from the standpoint of fiqh siyasah. This study is a juris-normative study, which is a legal study that is constructed conceptually through law-in-books by exploring legal and non-legal literature. According to the findings of this study, budget transparency in political parties is one aspect of achieving good governance. In fiqh siyasah, budget transparency is an obligation as ordered by Allah SWT through QS. al-Baqarah (2): 282 and 283. In addition, some hadiths describe the nature of Abu Bakr Ash Siddiq's openness in managing the finances of Baitul Mal. Therefore, transparency of the fund's budget is an obligatory effort by every political party in Indonesia to ensure good governance.